2023 clinical practice guidelines on autism spectrum disorder in children and adolescents in Singapore - Chui Mae Wong; Mariam Aljunied; Daisy Kwai Lin Chan; Janice Mun Yi Cheong; Bernard Chew; Chee Hon Chin; Sylvia Henn Tean Choo; Angelia Hwee Ling Chua; Magdalene Tze Suang Foo; Tze Jui Goh; Majeed Khader; Stephenie Koon Miang Khoo; et al. (Annals, Academy of Medicine, Singapore, 2024)
Introduction: Autism is a neurodevelopmental condition that is increasing in prevalence worldwide. There has been an exponential increase in autism-related research since 2010, when the first Singapore Clinical Practice Guidelines (CPG) on autism was published. Understanding of autism has since evolved to adopt a lifespan approach beyond that of a childhood condition. The aim of this CPG was to provide an updated set of recommendations for children and adolescents to aid clinical practice for professionals. Method: A multidisciplinary workgroup that comprised representatives from various sectors worked on this CPG. Clinical questions were organised into 10 different sections, each with its own subgroup of members. Seventeen existing international guidelines were evaluated using the Appraisal of Guidelines for REsearch & Evaluation II (AGREE-II) framework, of which 4 met criteria to act as references. Literature review across multiple databases was conducted between January 2011 to 2023; Grading of Recommendations, Assessment, Development and Evaluation (GRADE-like) methodology was used to synthesise evidence. Recommendation statements were derived, following Delphi-style consensus surveys among the workgroup. The draft guidelines underwent external review and public consultation before being formalised. Results: Recommendation and good practice statements pertaining to care of children and adolescents on the autism spectrum across 10 different sections were developed. Evidence matrices complement these recommendations and detail relevant evidence behind each recommendation statement. Conclusion: It is intended for these guidelines to promote effective management and healthcare services for children and adolescents on the autism spectrum, by reinforcing good and evidence-based clinical practice within our national context.